2021
DOI: 10.3390/children8010048
|View full text |Cite
|
Sign up to set email alerts
|

AQP1-Driven Migration Is Independent of Other Known Adverse Factors but Requires a Hypoxic Undifferentiated Cell Profile in Neuroblastoma

Abstract: Neuroblastoma is a biologically very heterogeneous tumor with its clinical manifestation ranging from spontaneous regression to highly aggressive metastatic disease. Several adverse factors have been linked to oncogenesis, tumor progression and metastases of neuroblastoma including NMYC amplification, the neural adhesion molecule NCAM, as well as CXCR4 as a promoter of metastases. In this study, we investigate to what extent the expression of AQP1 in neuroblastoma correlates with changing cellular factors such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…A classic example is the cell line SH-SY5Y that can be differentiated from ever-changing neuroblasts into mature neurons [ 31 ]. Our previous research has shown that even simple factors such as, e.g., cell density, can influence vital prognostic factors [ 28 ]. Moreover, hypoxia can significantly increase known adverse factors in neuroblastoma such as NMYC, CXCR4, PGK1 and AQP1, amongst others, leading to tumor progression and increased metastases [ 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A classic example is the cell line SH-SY5Y that can be differentiated from ever-changing neuroblasts into mature neurons [ 31 ]. Our previous research has shown that even simple factors such as, e.g., cell density, can influence vital prognostic factors [ 28 ]. Moreover, hypoxia can significantly increase known adverse factors in neuroblastoma such as NMYC, CXCR4, PGK1 and AQP1, amongst others, leading to tumor progression and increased metastases [ 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous research has shown that even simple factors such as, e.g., cell density, can influence vital prognostic factors [ 28 ]. Moreover, hypoxia can significantly increase known adverse factors in neuroblastoma such as NMYC, CXCR4, PGK1 and AQP1, amongst others, leading to tumor progression and increased metastases [ 25 , 26 , 27 , 28 ]. Neuroblastoma cells are characterized by changing biological behavior; a heterogeneous tumor microenvironment with stroma-rich or stroma-poor features; the presence or absence of immunomarkers such as GD2; adverse factors such as NMYC; or adhesion factors such as NCAM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Under hypoxic conditions, HIF-1α is upregulated and activates cellular responses to low oxygen levels [ 27 , 28 ]. Recent studies suggest that AQP1 expression is upregulated by a HIF-1α increase as a result of hypoxic conditions [ 29 , 30 , 31 , 32 , 33 ]. On the other hand, the upregulation of HIF-1α in the lungs under hypoxic conditions was inhibited in AQP1-knockout mice [ 34 ], suggesting a feedback mechanism between HIF-1α and AQP1 expression.…”
Section: Introductionmentioning
confidence: 99%